The influence of family environment and social environment on entrepreneurial interest among agribusiness management students - Al Ayyubi, Waridad Umais; Yanuan Putra, Mohammad Edwinsyah; Firmansyah, Akbar Maulana; Hidayat, Taufik (Institute of Computer Science (IOCS), 2025)
This study analyzes the influence of family and social environments on the entrepreneurial intention of Agribusiness Management students. The research employs a quantitative approach, surveying 29 students from the second and fourth semesters. Structured questionnaires were used to collect data, focusing on two independent variables: the family environment and the social environment, and their impact on students' entrepreneurial aspirations. The results show that a supportive and stimulating environment within both family and social contexts significantly enhances students' motivation to engage in entrepreneurial ventures. Together, these two environments explain 75.4% of the variation in entrepreneurial interest, as indicated by an R square value of 0.754. Specifically, the family environment, which includes elements such as parental guidance, family relationships, home atmosphere, economic status, and cultural background, accounts for 38.25% of the variance in entrepreneurial interest. Furthermore, the social environment, which encompasses peer interactions, relationships with faculty, and the overall university setting, contributes 37.13% to the development of entrepreneurial intent. The study acknowledges the limitations of a small sample size, which restricts the generalizability of the findings, and recommends further research with a larger and more diverse population across multiple institutions.